Sinosenecio ranunculoides (Asteraceae), a new species from Northeastern Jiangxi, Eastern China - She, Shi-Qi; Zhou, Xin; Xie, Wen-Yuan; Yao, Shen-Hao; Wang, Shao-Ping; Zhu, Hua-Min; Chen, Zheng-Hai; Jin, Xiao-Feng; Xu, Yue-Liang (Phytotaxa, 2025)
Sinosenecio ranunculoides (Asteraceae, Senecioneae), a new species from northeastern Jiangxi, China, is described on the basis of morphological and molecular evidence. This narrowly endemic species shares leafy stems and absent pappus with S. palmatisectus, S. phalacrocarpus and S. globigerus, yet it is clearly distinguished by its Ranunculus-like leaves with dense white arachnoid hairs on the adaxial surface, 5-ribbed hollow stems, biseriate phyllaries, and achenes that are densely covered with clavate trichomes and prominently 9-ribbed. Phylogenetic analysis using nuclear ribosomal DNA internal transcribed spacer (ITS) sequences confirms the placement of S. ranunculoides within the S. oldhamianus-Nemosenecio clade and supports its recognition as a distinct species, separate from all other members of this section.